Time, monetary and other costs of participation in family-based child weight management interventions: qualitative and systematic review evidence. - Lisa Arai; Monica Panca; Steve Morris; Katherine Curtis-Tyler; Patricia J Lucas; Helen M Roberts (PLoS ONE, 2015)
Background Childhood overweight and obesity have health and economic impacts on individuals and the wider society. Families participating in weight management programmes may foresee or experience monetary and other costs which deter them from signing up to or completing programmes. This is recognised in the health economics literature, though within this sparse body of work, costs to families are often narrowly defined and not fully accounted for. A societal perspective incorporating a broader array of costs may provide a more accurate picture. This paper brings together a review of the health economics literature on the costs to families attending child weight management programmes with qualitative data from families participating in a programme to manage child overweight and obesity. Methods A search identified economic evaluation studies of lifestyle interventions in childhood obesity. The qualitative work drew on interviews with families who attended a weight management intervention in three UK regions. Results We identified four cost-effectiveness analyses that include information on costs to families. These were categorised as direct (e.g. monetary) and indirect (e.g. time) costs. Our analysis of qualitative data demonstrated that, for families who attended the programme, costs were associated both with participation on the scheme and with maintaining a healthy lifestyle afterwards. Respondents reported three kinds of cost: time-related, social/emotional and monetary. Conclusion Societal approaches to measuring cost-effectiveness provide a framework for assessing the monetary and non-monetary costs borne by participants attending treatment programmes. From this perspective, all costs should be considered in any analysis of cost-effectiveness. Our data suggest that family costs are important, and may act as a barrier to the uptake, completion and maintenance of behaviours to reduce child obesity. These findings have implications for the development and implementation of child weight initiatives in particular, in relation to reducing inequalities in health.